Characterization of the first microRNA in human CDH1 that affects cell cycle and apoptosis and indicates breast cancers progression. Issue 3 (8th January 2022) - Gharbi, Sedigheh; Mohammadi, Zahra; Dezaki, Maryam Saedi; Dokanehiifard, Sadat; Dabiri, Shahriar; Korsching, Eberhard
Abstract: The E‐cadherin protein (Cadherin 1, gene: CDH1 ), a master regulator of the human epithelial homeostasis, contributes to the epithelial‐mesenchymal transition (EMT) which confers cell migratory features to the cells. The EMT is central to many pathophysiological changes in cancer. Therefore, a better understanding of this regulatory scenario is beneficial for therapeutic regiments. The CDH1 gene is approximately 100 kbp long and consists of 16 exons with a relatively large second intron. Since none microRNA (miRNA) has been identified in CDH1 up to now we screened the CDH1 gene for promising miRNA hairpin structures in silico. Out of the 27 hairpin structures we identified, one stable RNA fold with a promising sequence motive was selected for experimental verification. The exogenous validation of the hairpin sequence was performed by transfection of HEK293T cells and the mature miRNA sequences could be verified by quantitative polymerase chain reaction. The endogenous expression of the mature miRNA provisionally named CDH1‐i2‐miR‐1 could be confirmed in two normal (HEK293T, HUVEK) and five cancer cell lines (MCF7, MDA‐MB‐231, SW480, HT‐29, A549). The functional characterization by the 3‐(4, 5‐dimethylthiazol‐2‐yl)−2, 5‐diphenyltetrazolium bromide assay showed a suppression of HEK293T cell proliferation. A flow cytometry‐based approach showed the ability of CDH1‐i2‐miR‐1 to arrest transfected cells on a G2/M state while annexin staining exemplified an apoptotic effect. BAX and PTEN expression levels were affected following the overexpression with the new miRNA. The in vivo expression level was assessed in 35 breast tumor tissues and their paired nonmalignant marginal part. A fourfold downregulation in the tumor specimens compared to their marginal controls could be observed. It can be concluded that the sequence of the hub gene CDH1 harbors at least one miRNA but eventually even more relevant for the pathophysiology of breast cancer.